Chemical composition of Homalomena occulta essential oil and molecular docking-ADMET evaluation against antimicrobial targets - Nguyen, Vinh Phu; Tran, Hoang Ha; Nguyen, Tran Thien Phu; Nguyen, Vu Bao Ngoc; Tran, Quang Huy; Nguyen, Dai Chau; Nguyen, Thi Thanh Hai; Phan, Tu Quy; Tran, Nhat Phong Dao; Nguyen, Thi Ai Nhung (Hue University Journal of Science: Natural Science, 2026)
Homalomena occulta (H. occulta) essential oil was obtained via steam distillation, and its chemical composition was characterised using gas chromatography-mass spectrometry (GC-MS) analysis. A total of 43 compounds, predominantly oxygenated monoterpenes with linalool (40.35%), terpinen-4-ol (8.54%), and a-terpineol (3.05%) as the most abundant components, were identified. These compounds were evaluated in silico through molecular docking simulations using MOE 2022.10 software against three antimicrobial-related targets associated with pathogenic strains, namely Streptococcus pyogenes (P0C0C7), Streptococcus pneumoniae (Q8DQF8), and Candida albicans (4ESW). Several promising candidates with strong predicted inhibitory potentials were identified and ranked for each target as follows: P0C0C7: 40 (–11.2 kcal.mol–1) > 27 (–11.0 kcal.mol–1) > 4 (–10.9 kcal.mol–1) » 36 (–10.9 kcal.mol–1) > 29 (–10.4 kcal.mol–1); Q8DQF8: 27 (–9.6 kcal.mol–1) > 29 (–9.4 kcal.mol–1) > 25 (–9.3 kcal.mol–1) ≈ 41 (–9.3 kcal.mol–1) > 36 (–9.2 kcal.mol–1); 4ESW 42 (–11.3 kcal.mol–1) > 38 (–10.8 kcal.mol–1) > 21 (–10.7 kcal.mol–1) > 32 (–10.3 kcal.mol–1) » 41 (–10.3 kcal.mol–1). A drug-likeness study based on Lipinski’s rule of five was generally favourable (MW < 500 Da for 43/43 compounds; logP < 5 for 41/43 compounds). The ADMET prediction results suggested good absorption and permeability, along with a low risk of major transporter- and metabolism-related issues. Overall, these findings provide a strong in silico basis, supporting further experimental antimicrobial testing for H. occulta essential oil.